Shedding of Klotho: Functional Implications in Chronic Kidney Disease and Associated Vascular Disease - Saar-Kovrov, Valeria; Donners, Marjo M. P. C.; van der Vorst, Emiel P. C. (Frontiers in Cardiovascular Medicine, 2021)
α-Klotho (Klotho) exists in two different forms, a membrane-bound and soluble form, which are highly expressed in the kidney. Both forms play an important role in various physiological and pathophysiological processes. Recently, it has been identified that soluble Klotho arises exclusively from shedding or proteolytic cleavage. In this review, we will highlight the mechanisms underlying the shedding of Klotho and the functional effects of soluble Klotho, especially in CKD and the associated cardiovascular complications. Klotho can be cleaved by a process called shedding, releasing the ectodomain of the transmembrane protein. A disintegrin and metalloproteases ADAM10 and ADAM17 have been demonstrated to be mainly responsible for this shedding, resulting in either full-length fragments or sub-fragments called KL1 and KL2. Reduced levels of soluble Klotho has been associated with kidney disease, especially chronic kidney disease (CKD). In line with a protective effect of soluble Klotho in vascular function and calcification, CKD and the reduced levels of soluble Klotho herein are associated with cardiovascular complications. Interestingly, although it has been demonstrated that soluble Klotho has a multitude of effects its direct impact on vascular cells and the exact underlying mechanisms remain largely unknown and should therefore be a major focus of further research. Moreover, functional implications of the cleavage process resulting in KL1 and KL2 fragments remain to be elucidated.